Islamic Indonesian EFL students’ responses on English-speaking countries - Yustina, Luli Sari; Sukandi, Syayid Sandi; Arniman, Nurkhairat (Englisia Journal, 2021)
EFL students learn English within the notion of English as an international language. The gap in this research is to study the learning of English as a language to the study of the culture of the English-speaking countries. This gap emerged after cross-culture understanding was taught in a one-semester course at an Islamic state university in Indonesia. Phenomenology is the theory used in this research, within the qualitative research approach and descriptive statistics. 110 respondents were given the questionnaires, with open-ended questions asking four interrelated questions about the United States of America, the United Kingdom, and Australia as the three English-speaking countries. The respondents’ answers in the questionnaire were analysed by using codes, or themes, that later on show the frequency of each theme. The answers were categorized according to the themes and the percentage based on frequency. Thus, the findings of this research highlighted that Indonesian Muslim students have certain themes when looking at English-speaking countries, such as the United States of America, the United Kingdom, and Australia when they learn English as a foreign language.